1998
DOI: 10.1038/sj.ejcn.1600511
|View full text |Cite
|
Sign up to set email alerts
|

Low cereal intake in Estonian infants: the possible explanation for the low frequency of coeliac disease in Estonia

Abstract: Objective: The aim of this study was to analyse the intake of coeliac disease (CD) inducing, gluten containing cereals (wheat, rye, barley and oats) in Estonian infants diet and compare these results with neighbouring countries with different CD incidence rate. Design: Study group consisted of 32 healthy full term infants of Estonian origin. Settings: Study was carried out in Tartu University Women's Hospital and in Tartu University Children's Hospital. These are both primary care facilities. Subjects: Infants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 8 publications
0
10
0
2
Order By: Relevance
“…Misclassification may explain why the studies did not find an association between age at gluten introduction and celiac disease. It has been previously proposed that an abrupt introduction of a high amount of gluten in infant feeding has an effect on celiac disease [12][13][14][15][16][17][18]. However, the quantitative effect of gluten could not be investigated with our retrospective study design.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Misclassification may explain why the studies did not find an association between age at gluten introduction and celiac disease. It has been previously proposed that an abrupt introduction of a high amount of gluten in infant feeding has an effect on celiac disease [12][13][14][15][16][17][18]. However, the quantitative effect of gluten could not be investigated with our retrospective study design.…”
Section: Discussionmentioning
confidence: 54%
“…Further, the Swedish National Health Office recommended a delay in the age of gluten introduction from 4 to 6 months [12,13]. In order to investigate why the incidence of celiac disease increased in Sweden, at the same time there was no corresponding increase in neighboring countries, several comparative studies of infant feeding habits were undertaken [12][13][14][15][16][17][18]. Data from healthy infants showed that the amount of gluten in the infant diet was higher in Sweden, where the incidence of celiac disease is higher, as compared with its neighboring countries.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1980s such an approach demonstrated that the decline in incidence of celiac disease on the British Isles had been accompanied by changes in infant feeding [6,8]. In the 1990s celiac disease was more frequently reported for children in Sweden and Italy as compared to Finland, Denmark and Estonia, and infants in the former countries had a larger consumption of wheat gluten [14][15][16]. Also, a Swedish surveillance revealed an epidemic of celiac disease in children where changes in incidence had a temporal correlation with changes in infant feeding [17].…”
Section: Analytical Studies -Causality Assessmentmentioning
confidence: 99%
“…There was no difference in the amount of flour introduced in the first portion between cases with CD and healthy controls [18]. Several authors have also implicated divergent flour consumption as an explanation for the geographic differences in CD incidence in Europe [50,51,52]. Furthermore, it is known that the amount of gluten in the diet correlates with the mucosal damage [53,54], and we speculate that large amounts of gluten in the early non-breast milk diet could trigger more symptoms in children with CD and, thus, a diagnosis of CD.…”
Section: Amount Of Glutenmentioning
confidence: 99%